Rekomendasi Lokasi Pet Shop Di Kota Malang Menggunakan Metode Analytical Hierarchy Process (AHP) Simple Additive Weighting (SAW) - Ghiffary Rizal Hamdhani; Edy Santoso; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays raising animals like cats is like a lifestyle, sometimes many people think of the pet as family. Therefore pet owners always give the best care to the animals. This system uses one of the methods in the Decision Support System. Decision Support System is a computer-based system that can assist a person in improving its performance in decision making. By using one of the methods in the Decision Support System, it is expected to help solve problems that are in semi-structured areas such as the above problems. In this system will use the method of Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW). Analytical Hierarchy Process (AHP) is a method used to solve an unstructured complex situation into several components within hierarchical groups, by assigning subjective values and determining which variables have the highest priority to influence the outcomes in those situations . Simple Additive Weighting (SAW) is used for ranking.. Based on the results of the test can be analyzed that the AHP and SAW method is quite effective used in the recommendation process. The result of accuracy testing on custody service is 72,72% while accuracy testing of grooming service equal to 75%.